Ligand dynamics on the surface of CdSe nanocrystals. Issue 16 (28th March 2023) - Cosseddu, Salvatore; Pascazio, Roberta; Giansante, Carlo; Manna, Liberato; Infante, Ivan
Abstract : Classical molecular dynamics simulations can help understand the locations, binding modes and mobilities of carboxylate ligands on CdSe nanocrystals, aiding in the optimization of their overall performance and efficiency. Abstract : Synthesis protocols of colloidal semiconductor nanocrystals (NCs) comprise the coordination of the semiconductive inorganic core by a layer of organic ligands, which play a crucial role in stabilizing the NCs in organic solvents. Understanding the distribution, binding and mobility of ligands on the different NC facets is key to prevent the formation of surface defects and to optimize the overall optoelectronic efficiency of these materials. In this paper, we employed classical molecular dynamics (MD) simulations to shed light on the plausible locations, binding modes and mobilities of carboxylate ligands on the different facets of CdSe nanocrystals. Our results suggest that these features are influenced by the temperature of the system and the coordination number of the surface (Cd and Se) atoms. High ligand mobilities and structural rearrangements are linked to a low coordination of the Cd atoms. Undercoordinated Se atoms, which are considered the culprit of hole trap states in the bandgap of the material, are instead found to spontaneously form on the nanosecond timescale, making them likely candidates for an efficient photoluminescence quenching mechanism.